2020
DOI: 10.1111/hsc.13234
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of barriers to HIV prevention, treatment and support: Perspectives of transgender women and service providers

Abstract: Transgender (trans) women experience barriers to access to HIV care, which result in their lower engagement in HIV prevention, treatment and support relative to cisgender people living with HIV. Studies of trans women's barriers to HIV care have predominantly focused on perspectives of trans women, while barriers are most often described at provider, organisation and/or systems levels. Comparing perspectives of trans women and service providers may promote a shared vision for achieving health equity. Thus, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
15
0
4
Order By: Relevance
“…These findings demonstrate training PCPs to be more trans‐affirming and intersectionally inclusive utilizing evidence‐informed interventions is essential (e.g. [15, 41, 42]). Moreover, findings suggest the need for trans‐affirming support for TNB survivors of sexual violence, potentially fostered through integrating components of promising provider‐level interventions [43, 44] into training more broadly focused on HIV prevention and care for TNB persons, with the potential benefit of increasing access to HIV care [45].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings demonstrate training PCPs to be more trans‐affirming and intersectionally inclusive utilizing evidence‐informed interventions is essential (e.g. [15, 41, 42]). Moreover, findings suggest the need for trans‐affirming support for TNB survivors of sexual violence, potentially fostered through integrating components of promising provider‐level interventions [43, 44] into training more broadly focused on HIV prevention and care for TNB persons, with the potential benefit of increasing access to HIV care [45].…”
Section: Resultsmentioning
confidence: 98%
“…There are also gaps in understanding multi-level factors associated with HIV testing among TNB persons, particularly anti-trans stigma and gender affirmation. Quantitative studies have shown negative associations between anti-trans stigma and HIV care access [14], whereas qualitative studies have identified how intersecting anti-trans and HIV stigma limit trans women's access to HIV prevention/care [15].…”
Section: Introductionmentioning
confidence: 99%
“…Having a usual source of health care and comfort with a provider were associated with a higher likelihood of viral suppression, HIV testing, and PrEP use, all of which play key roles in HIV prevention. Comfort with a provider can help alleviate the stigma and discrimination that often deter transgender persons from seeking care ( 6 ). Perceived interactions with hormones, concerns about side effects, medical mistrust, competing priorities, and the belief that PrEP is specifically for gay men are all documented barriers to PrEP use among transgender persons ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…This information should be more routinely collected in affirming ways, taking into consideration best practices (e.g. self‐administered questionnaires), and be informed by intersectional considerations such as concerns about confidentiality and disclosure, particularly among trans women with precarious immigration status [17]. Gender‐affirming support for substance use is also urgently needed.…”
Section: Discussionmentioning
confidence: 99%